2008
DOI: 10.1111/j.1469-0691.2008.01953.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Yersinia pestis isolates from natural foci of plague in the Republic of Georgia, and their relationship to Y. pestis isolates from other countries

Abstract: Forty Yersinia pestis isolates from endemic foci of plague in the Republic of Georgia, and six Y. pestis isolates from neighbouring former Soviet Union countries, were analysed for their biochemical and phenotypic properties, and their genetic relatedness was compared with Y. pestis strains KIM and CO92 by pulsed-field gel electrophoresis (PFGE). In addition, 11 Y. pestis isolates from the USA, together with published nucleotide sequences from Y. pestis strains KIM, CO92 and 91001, were compared with the 46 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 32 publications
1
30
1
2
Order By: Relevance
“…Although PFGE sensitivity and discriminatory ability depend on the restriction enzyme and organism studied, its high performance has become valuable for typing many bacteria and discriminating Y. pestis strains Huang et al, 2002;Revazishvili et al, 2008;Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although PFGE sensitivity and discriminatory ability depend on the restriction enzyme and organism studied, its high performance has become valuable for typing many bacteria and discriminating Y. pestis strains Huang et al, 2002;Revazishvili et al, 2008;Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the strains could be inaccurate representatives of the original isolates, and these differences could be due to handling procedures during the prolonged storage of the strains in the laboratory since their isolation (Revazishvili et al, 2008;Vogler et al, 2011). Leal et al (2000) and Leal-Balbino et al (2004, 2006 observed spontaneous changes in the genome (both plasmid and chromosomal) of Brazilian Y. pestis following prolonged storage and laboratory handling.…”
Section: Discussionmentioning
confidence: 99%
“…orientalis) мутации приве-ли к возможности синтеза только укороченных до 147 и 130 аминокислотных остатков и, веро-ятно, функционально неполноценных вариан-тов белка Caf1. Секвенирование гена caf1 из 41 штамма, выделенного на территории Грузии и Армении от полевок и их эктопаразитов, пока-зало, что для них всех характерна замена A48 → S48, а штаммы, выделенные в этом же регионе от песчанок или сусликов, обладали канониче-ской последовательностью гена caf1 [79].…”
Section: рисунок 1 электронная микрофотография единичной клетки штамunclassified